Is There an Association between Platelet Count and Blood Loss in the Parturient? A Retrospective Study - Beilin, Yaakov; Liu, Helen; Hyers, Benjamin M.; Mijovic, Vasilije; Katz, Daniel (American Journal of Perinatology, 2023)
Objective The influence of thrombocytopenia on blood loss and postpartum hemorrhage (PPH) has been conflicting. Our aim was to determine if there is an association between predelivery platelet count and quantitative blood loss (QBL) and PPH in both vaginal (VD) and cesarean deliveries (CD).Study Design We conducted a retrospective database study at a single institution from April 1, 2017 to September 9, 2020. The platelet count closest to time of delivery and the QBL was assessed separately for VD and CD.Results A total of 22,479 records were reviewed, of which 16,822 (75%) were VD and 5,657 (25%) were CD. A total of 2,600 (12%) patients had thrombocytopenia, defined as a platelet count <150,000/mm3. Of these, 1,980 (76%) had a VD and 620 (24%) had CD. We found a statistically significant difference in QBL between parturients with thrombocytopenia compared with those without, with a median estimated difference in QBL of 25 (95% confidence interval [CI]: 16–32) and 57 mL (95% CI: 31–87) in VD and CD patients, respectively. We also found a statistically significant difference in QBL when comparing patients among all the platelet count ranges except in the lowest platelet count range of 50,000 to 69,999/mm3 with a mean difference of 52 (95% CI: 25–81) and 107 mL (95% CI: 39–180) in the VD and CD patients, respectively in the platelet count range of 70,000 to 99,999/mm3 . We also found the incidence of PPH was greater in those with thrombocytopenia, p < 0.001, but the median difference in QBL in all platelet groups was small.Conclusion We found a statistically significant association between lower predelivery platelet counts and QBL and PPH. The clinical significance of these results is debatable, because at all platelet count ranges, differences in blood loss were small.Key Points
Keywords: parturient; thrombocytopenia; quantitative blood loss; platelet count; postpartum hemorrhage